2013
DOI: 10.1007/s00170-012-4713-z
|View full text |Cite
|
Sign up to set email alerts
|

Artificial neural network prediction of weld distortion rectification using a travelling induction coil

Abstract: An experimental investigation has been carried out to determine the applicability of an induction heating process with a travelling induction coil for the rectification of angular welding distortion. The results obtained from experimentation have been used to create artificial neural network models with the ability to predict the welding induced distortion and the distortion rectification achieved using a travelling induction coil.The experimental results have shown the ability to reduce the angular distortion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…The software used throughout this study was NeuroSolutions, which had previously been used by the authors for the successful prediction of weld geometry [1], distortion [22] and distortion rectification [24]. A total of 360 datasets were produced, 36 for each nozzle and shielding gas configuration, with an additional 20 for validation/production, thus allowing for a full range of results ranging from good quality welds performed using a low shielding gas flow rate and no cross draft, to poor quality welds with a high shielding gas flow rate and high cross draft velocity.…”
Section: Ann Model Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The software used throughout this study was NeuroSolutions, which had previously been used by the authors for the successful prediction of weld geometry [1], distortion [22] and distortion rectification [24]. A total of 360 datasets were produced, 36 for each nozzle and shielding gas configuration, with an additional 20 for validation/production, thus allowing for a full range of results ranging from good quality welds performed using a low shielding gas flow rate and no cross draft, to poor quality welds with a high shielding gas flow rate and high cross draft velocity.…”
Section: Ann Model Developmentmentioning
confidence: 99%
“…ANN models have been applied extensively and relatively widespread to the welding process, predicting a number of weld aspects, including weld geometry, 1,17 mechanical properties, 18,19 weld quality, 20,21 weld-induced distortion 22,23 and weld distortion rectification. 24…”
Section: Introductionmentioning
confidence: 99%
“…They employed a set of FEM results obtained for various plate dimensions as the ANN inputs. Barclay et al [13] investigated the suitability of the induction heating process with the traveling induction coil to rectify the welding angular distortion. By using the experimental data, they considered an ANN to predict the distortion.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, residual stresses are introduced to the surrounding material, resulting in distortion in the final welded structures; a common problem associated with any welding process [24]. Although it has been shown that there is a critical limit to the angular distortion due to the welding process [25], the magnitude of the weld-induced distortion is primarily related to the specific thermal energy input of the welding process [26].…”
Section: Introductionmentioning
confidence: 99%
“…Computational modelling has become increasingly popular over the past few decades for the prediction of various aspects of the welding process. Extensive studies have been conducted in areas fundamental to the final structure, namely residual stresses in the weld region [29,30,31], weld induced distortion [25,26,30,31] and the solidified weld geometry [10,31].…”
Section: Introductionmentioning
confidence: 99%